Beta-defensins-2 expressions in gingival epithelium cells after probiotic Lactobacillus reuteri induction - Tuti Kusumaningsih (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Beta-defensins (BD) are antimicrobial peptides that play a role in defense against pathogens. Beta-defensins (BD) are expressed by a variety of epithelial cells, including gingival epithelium, salivary glands, saliva and salivary duct. BD-1 is expressed constitutively, while BD-2 and BD-3 expressions can be induced by commensal bacteria. Probiotics are commensal bacteria, thus L. reuteri as probiotic bacteria may act as “inducer” for BD-2 in epithelial gingiva. S. mutans is the main bacteria causing dental caries and sensitive to BD-2. Purpose: This study was aimed to prove that the administration of probiotic L. reuteri may improve BD-2 expressions in the gingiva epithelium. Method: This study was conducted in vivo using twenty-four male Rattus norvegicus Wistar strains aged 10-12 weeks and weighed 120-150 g. Those rats were randomly divided into four groups, namely negative control group (not induced with L. reuteri or S. mutans), positive control group (induced with S. mutans for 14 days), treatment group 1 (induced with L. reuteri for 14 days and S. mutans for 7 days), and treatment group 2 (induced with L. reuteri and S. mutans for 14 days concurrently). The concentration of L. reuteri used was 4x108cfu/ml, while the concentration of S. mutans was 1x 1010cfu/ml. 0.1 ml of each was dropped in the region of the mandibular incisors. BD-2 expression was calculated using immunohistochemical method. The difference of BD-2 expressions in gingival epithelial cells in the respective groups was analyzed by Anova/SPSS. Results: There were significant differences in BD-2 expressions in gingival epithelial cells in each group based on the results of Anova test (p=0.001). Conclusion: The administration of probiotic L. reuteri is able to increase BD-2 expressions in gingival epithelial cells.